Dinamika Penyelesaian Harta Bersama: Perbedaan Pandangan Tokoh Agama di Kecamatan Bagan Sinembah - Asqia Az-zahra, Indi; Milhan (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
The ideal division of shared property, as stipulated in Article 96, Paragraph 1 of the Compilation of Islamic Law (KHI), mandates an equitable division of two equal parts in the event of divorce. However, the reality in Bagan Sinembah reveals prolonged delays in resolving shared property issues, attributed to a lack of understanding and legal socialization. This study aims to explore the dynamics and challenges of applying shared property laws in the region. The article is a literature-based study with a qualitative approach, employing empirical legal research and socio-legal analysis. The research findings reveal that the dynamics of shared property division in Bagan Sinembah highlight challenges in legal implementation, particularly concerning prolonged delays. Differences in opinion among religious leaders regarding the division of shared property contribute to this issue. Some religious leaders believe that the husband has the right to use shared property without involving the children, while others refer to QS. An-Nisa, verse 10, which addresses the rights of children in inheritance.